2019
DOI: 10.31545/intagr/112023
|View full text |Cite
|
Sign up to set email alerts
|

Mineral nitrogen content in hydrographic areas of Poland depending on land use

Abstract: A b s t r a c t. One unintended consequence of nitrogen use in agriculture is an increase in nitrate content in ground waters. Nitrogen content was evaluated in soil samples from specific hydrographic regions of Poland from the 60-90 cm soil layer, in which this nutrient is not readily available to the main root mass of crop plants and may negatively affect the environment. It was revealed that N min content in specific hydrographic regions was highly dependent on both the soil type and land use. Notably highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Nitrogen in soils belongs to active and dynamic elements. Its content in the surface horizon of soils in Poland has been estimated to be from 0.02% to 0.035% and depends on a number of factors, including the climate ones [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen in soils belongs to active and dynamic elements. Its content in the surface horizon of soils in Poland has been estimated to be from 0.02% to 0.035% and depends on a number of factors, including the climate ones [33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Part of the SMN was absorbed by the wheat. However, N is not taken up from the deeper soil layers until wheat roots have formed [30]. The unusually warm winter was likely to have contributed to SMN losses.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in mineral nitrogen in soil was due to the nitrogen-rich and rapidly decomposing (C:N < 15) mass of forage legumes incorporated during ploughing [ 9 ]. Previous studies showed that in the conditions of variable humidity in autumn, most of the mineral nitrogen accumulates in the deeper layer (30–60 cm) after ploughing in forage legume mass [ 9 ], and usually this nitrogen is not available, as the main cereal roots have not yet formed [ 38 ]. Therefore, during such a period, there is a risk of nitrogen migration into deeper soil layers and its leaching [ 10 ].…”
Section: Discussionmentioning
confidence: 99%